Larger Resin Ducts Are Linked to the Survival of Lodgepole Pine Trees During Mountain Pine Beetle Outbreak - Zhao, Shiyang; Erbilgin, Nadir (Frontiers in Plant Science, 2019)
Periodic mountain pine beetle outbreaks have killed millions of hectares of lodgepole pine forests in western North America. Within these forests often some pine trees remain alive. Studies have mainly focused on the tree chemical defenses to explain host tree resistance to bark beetles, but it has been rarely documented whether anatomical defenses differ between beetle-killed and live residual pine trees, especially at the northern latitudinal range of beetles in North America. Resin ducts, as important components of anatomical defenses, are responsible for production, storage, and translocation of resins to the site of beetle attacks. We compared the resin duct-based anatomic defenses and radial growth between beetle-killed and live residual lodgepole pine trees and characterized the resin ducts and growth of the residual trees before, and after outbreak. We further categorized residual trees as healthy (having no signs or symptoms of insect or pathogen attacks), declining (with signs or symptoms of biotic attacks), and survived (from mountain pine beetle attacks during outbreak). We built logistic models to predict the probability of survival of lodgepole pine trees during beetle outbreaks using the resin duct characteristics and radial growth of beetle-killed and residual trees. We found that residual trees had larger resin ducts prior to outbreaks and continued having so after outbreak in post-outbreak stands. Tree radial growth (ring width) was not associated with tree survival. Furthermore, healthy trees consistently had larger resin ducts than those trees showing declining symptoms in the past 20 years in post-outbreak stands. Survival trees ranked between healthy and declining trees. Overall, these results demonstrate that resin duct size of lodgepole pine trees can be an important component of tree defenses against MPB attacks and suggest that lodgepole pine trees with large resin ducts are likely to show resistance to future bark beetle attacks.